Behavioral and psychopharmacologic pain management - Ebert, Michael H.; Kerns, Robert D., 1950- (Cambridge University Press, 2010)
"Pain is the most common symptom bringing a patient to a physician's attention. Physicians training in pain medicine may originate from different disciplines and approach the field with varying backgrounds and experience. This book captures the theory and evidence-based practice of behavioral, psychotherapeutic and psychopharmacological treatments in modern pain medicine. The book's contributors span the fields of psychiatry, psychology, anesthesia, neurology, physical medicine and rehabilitation, and nursing. Thus the structure and content of the book convey the interdisciplinary approach that is the current standard for the successful practice of pain management. The book is designed to be used as a text for training fellowships in pain medicine, as well as graduate courses in psychology, nursing, and other health professions"--Provided by publisher.